Sumber Daya Perusahaan dalam Teori Resource-based View - Fransisca Mulyono (Jurnal Administrasi Bisnis, 2013)
Resource - based view theory is a theory that is prominent in the strategic manage-ment field since the early 1990s . Principally due to the prominence of this theorythat prioritizes the role of internal resources that when certain conditions are metwill bring the company gain the competitive advantage even sustainable competitiveadvantage that will lead to superior performance .Resources in general consists of tangible and intangible resources. Intangibleresources according to many researchers is the strategic resources because these re-sources which will bring the company is able to achieve competitive advantage andsustainable.competitive advantage .This paper seeks to describe the elements of intangible resources includingthe factors or indicators . expressed in this paper are four elements of intangibleresources, namely human capital , structural capital , relational capital and customercapital . It also depicted on the properties required in the intangible resources thatsustainable competitive advantage can be achieved by the company.Keywords: firm resources, resource-based theory.